2022
DOI: 10.3389/fonc.2022.1039366
|View full text |Cite
|
Sign up to set email alerts
|

LINC00324 in cancer: Regulatory and therapeutic implications

Abstract: LINC00324 is a 2082 bp intergenic noncoding RNA. Aberrant expression of LINC00324 was associated with the risk of 11 tumors and was closely associated with clinicopathological features and prognostic levels of 7 tumors. LINC00324 can sponge multiple miRNAs to form complex ceRNA networks, and can also recruit transcription factors and bind RNA-binding protein HuR, thereby regulating the expression of a number of downstream protein-coding genes. LINC00324 is involved in 4 signaling pathways, including the PI3K/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In addition to its classic function of complex ceRNA network forming, LINC00324 can also bind RNA-binding proteins and recruit transcription factors in order to regulate multiple downstream gene expressions [ 41 ]. Although no relevant studies have been conducted in CM, LINC00324 has been shown to be overexpressed in a variety of cancer types and to be associated with pathologic features and risk stratification [ 42 ]. Unlike most tumor types, we observed a significant reduction in LINC00324 mRNA level in the A375 melanoma cell line compared to the HFB4 control cell line, which is in line with the observation in breast cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its classic function of complex ceRNA network forming, LINC00324 can also bind RNA-binding proteins and recruit transcription factors in order to regulate multiple downstream gene expressions [ 41 ]. Although no relevant studies have been conducted in CM, LINC00324 has been shown to be overexpressed in a variety of cancer types and to be associated with pathologic features and risk stratification [ 42 ]. Unlike most tumor types, we observed a significant reduction in LINC00324 mRNA level in the A375 melanoma cell line compared to the HFB4 control cell line, which is in line with the observation in breast cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are non-coding RNA sequences that sponge and sequester microRNAs (miRNAs). Both lncRNAs and miRNAs regulate important cell processes in cancerous and noncancerous diseases [ 112 , 113 , 114 , 115 ]. It has been reported that lncRNA ADAMTS9-AS1 plays a key role in the progression and development of several types of cancer, including lung [ 116 ], glioma [ 117 ], bladder [ 118 ], breast [ 119 ] and prostate [ 119 ].…”
Section: Intracellular Modulators Of Slc7a11 In Ovarian Cancermentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are RNA sequences which do not code any polypeptide or protein and act by sponging and sequestering micro RNAs (miRNAs). Both miRNAs and lncRNAs play a key role in cancerous and non-cancerous diseases [62][63][64][65][66]. LncRNA H19 is encoded by the H19 gene and plays a key role in cancer onset and progression modulating cell growth, invasion and migration [67].…”
Section: Nqo1 Cellular Modulators In Ovarian Cancermentioning
confidence: 99%